Evaluasi Kinerja UMKM Ditinjau Dari Aspek Keuangan Dan Aspek Pemasaran Pasca Pandemi Covid 19 - Komala Ardiyani; Amalia Ilmiani; Muhammad Maulidin Fachrur (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This study aims to provide empirical evidence regarding the importance of evaluating theperformance of MSMEs after the Covid-19 pandemic. Using financial aspects and marketingaspects, the study tries to examine the extent to which financial and marketing aspects affect theperformance of MSMEs. A total of 75 Batik SMEs domiciled in Pekalongan City participated in thisstudy. The analysis technique used is multiple linear regression with hypothesis testing.The results of the study revealed that the financial aspect and the marketing aspect contributed tothe improvement of the performance of Batik UMKM after the Covid 19 pandemic, so that theproposed hypothesis was supported. The financial aspect has a significant positive effect on theperformance of MSMEs, as well as the marketing aspect has a significant positive effect on theperformance of MSMEs.Developing countries such as Indonesia see MSMEs as a way out of poverty so it is necessary tocreate superior MSMEs so that they can compete in the global market. Great attention throughfinancial and marketing aspects can realize competitive small and medium scale industries.